Pollination ecology of Lantana camara and its relationship with honey bees (Apis mellifera scutellata) in South Africa - Pirk, Christian Walter Werner (University of Pretoria, 2023)
Dissertation (MSc (Entomology))--University of Pretoria, 2023.